Invasive physiologic assessment of coronary artery stenosis by resting full-cycle ratio and fractional flow reserve: a prospective observational study - Oh-Hyun Lee; Ji Woong Roh; Yongcheol Kim; Seok-Jae Heo; Eui Im; Deok-Kyu Cho (Scientific Reports, 2023)
Abstract Resting full-cycle ratio (RFR), an alternative to fractional flow reserve (FFR) for evaluating intermediate coronary artery stenosis, helps reduce patients’ time, cost, and discomfort. However, the validation data for RFR and FFR are lacking. We aimed to assess the diagnostic accuracy of RFR and FFR and evaluate effective decision-making for revascularization using their values. Patients subjected to an invasive physiological study for intermediate coronary artery stenosis in Yongin Severance hospital between October 2020 and April 2022 were prospectively and consecutively recruited. We evaluated the correlation between RFR and FFR measurements and the diagnostic performance of RFR (≤ 0.89) versus FFR (≤ 0.80). In all, 474 intermediate coronary stenosis lesions from 400 patients were evaluated using RFR and FFR values. There was a strong linear relationship between RFR and FFR (r = 0.75, 95% CI 0.70–0.78, p < 0.01). Comparing diagnostic performance between RFR and FFR, RFR demonstrated diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of 85.0%, 80.0%, 86.7%, 67.1%, and 92.7%, respectively. We analyzed the RFR value in the hyperemia zone (0.86–0.93) according to positive (RFR: 0.86–0.89) and negative (RFR: 0.90–0.93) areas. PPV in positive area is 47.8% (95% Confidence Interval [CI]: 33.8% to 62.0%) and NPV in negative area is 87.7% (95% CI: 80.3% to 93.1%). Excellent correlation exists between RFR and FFR and the diagnostic value of RFR without hyperemia compared with FFR in establishing the accurate functional significance of coronary artery stenosis was shown. RFR alone could evaluate the functional significance of coronary artery stenosis without unnecessary hyperemia, except in the positive area. Trial registration: URL: http://trialsearch.who.int ; Unique identifier: KCT0005255.